Criticizing Israel Is Not Antisemitism. Issue 1 (1st March 2019) - Bindman, Geoffrey
Abstract : Antisemitism is hostility to Jews as Jews, but defining antisemitism is complicated by Zionism and the existence of the State of Israel. The fundamental right to freedom of expression is threatened by the misuse of a definition of antisemitism and claimed examples of antisemitic conduct that encourage confusion between antisemitism and criticism of the policies and practices of the Israeli government and its institutions. The right to express criticism and to debate such policies and practices must not be suppressed by reliance on unsubstantiated claims of antisemitism.